Online English Dictionaries: An Overview of the Characteristics of Three Dictionaries and an Analysis of Their Suitability for Students - Todorović, Milan D.; Spasić, Nataša A. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
In this paper we have scrutinized three popular monolingual English dictionaries: Longman Dictionary of Contemporary English Online, Oxford Learner’s Dictionaries, and Merriam–Webster Dictionary, the online versions of the printed Longman Dictionary of Contemporary English, Oxford Advanced Learner’s Dictionary and Merriam–Webster’s Collegiate Dictionary. After the introductory part, consisting of a short overview of the general nature and importance of (online) dictionaries in the classroom, we have presented general characteristics that all observed dictionaries have in common. Following this, a more in-depth analysis of the intricacies of the three dictionaries has been given. We have studied the additional functions that each of the dictionaries has (the thesaurus, synonymous expressions, fun facts, quizzes, grammar exercises, etc.). Finally, we have established a connection between this technological innovation and the classroom itself. We have used three factors to determine the suitability and influence of each dictionary: (a) economy; (b) interactivity; (c) simplicity. Our aim was to determine the importance and effectiveness of modern technologies, so that their potential can be implemented in education. Based on the observed data, we can conclude that LDCEO and OLD (given their pedagogical purposes) are more suitable dictionaries for students of English as a foreign language on the primary and high school levels, while MWD, due to its purpose, complexity of language and other advanced features is more suitable for students on higher levels of education.